2020
DOI: 10.3390/ijerph17165937
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Psychosocial Wellbeing in the Context of Complex and Multidimensional Problems

Abstract: This Special Issue deals with the topic of how people and social groups face problems in an increasingly complex and globalized society. The topics included in the call for papers were the interaction of psychosocial well-being and mental health with economic, gender, racial and ethnic inequalities, migration and demographic change and conflict and war, as well as the effects of stigma on people discriminated against because of their differential characteristics, whether they are of a sexual, disability or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Psychosocial well-being is an integral part of health as defined by the World Health Organization (WHO) [18] and represents a multidimensional construct which incorporates emotional, social, and physical aspects [19]. Adverse psychosocial well-being has been associated with water insecurity [15][16][17], with findings implying that high water insecurity relates to increased emotional distress [15,17] and lower quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial well-being is an integral part of health as defined by the World Health Organization (WHO) [18] and represents a multidimensional construct which incorporates emotional, social, and physical aspects [19]. Adverse psychosocial well-being has been associated with water insecurity [15][16][17], with findings implying that high water insecurity relates to increased emotional distress [15,17] and lower quality of life [16].…”
Section: Introductionmentioning
confidence: 99%
“…To adjust to the re-entry phase, patients mostly used cognitive coping, followed by behavioral coping and avoidant coping. [18] Patients who had received psychoeducation aimed at coping in the re-entry phase showed greater use of cognitive and behavioral coping compared with the control group and subsequently had less mood disturbance. [18] Studies that reported on the re-entry fading into early survivorship phase and used standardized questionnaires found…”
Section: Mental Adjustment To the Re-entry Phasementioning
confidence: 95%
“…Recent research has found that some important psychosocial factors, such as general concerns over COVID-19 and racial/ethnic discrimination, contribute to suicide risk among U.S. college students ( Oh et al, 2022 ). Additionally, college students’ wellness encompasses other essential psychosocial components, such as mental health, academics, and food security ( Eiroa-Orosa, 2020 ). We wondered if these psychosocial factors might also predict suicidal thoughts and behaviors among U.S. college students during the pandemic.…”
Section: Introductionmentioning
confidence: 99%